The Nature of God: Theological Debate and Implications of the Tauhid’s Sentences - Saenong, M. Kafrawy; Santalia, Indo; Jafar, Usman; Irmawati, Irmawati; Huda, Khairul (CV. Tripe Konsultan, 2024)
The research aims to discuss the debate between the Asy'ariyah and Mu'tazilah about the nature of God. The method used literature study from various sources. The results of this research show that there are the differences between Mu`tazilites and al-Ash`ari in Divine Aspects in Theology. First, The Nature of God. The Mu`tazilites stated that Allah is All-Knowing with His substance, not with knowledge, power and life because all of these are qualities while nature is something outside of substance. Meanwhile, the Asy` believe that God has attributes. Second, The God's Justice, the Mu`tazilites elive that all of God's actions are good, God does not do bad, and does not forget what He must do. On the other hand al-Ash`ari they are not realized by humans themselves, but are created by God. Three, God's Absolute Power and Will , the Mu`tazilah argued that God's power is actually no longer absolute. On the other side, the Asy'ariyah were unable to reach the depth of monotheism fi'li while the Mu'tazilah were unable to resolve issues of justice in the right way.